2020
DOI: 10.3390/cancers12102726
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Profiling Reveals That the Deregulation of H19, WT1-AS, TCL6, and LEF1-AS1 Is Associated with Higher-Risk Myelodysplastic Syndrome

Abstract: Background: myelodysplastic syndrome (MDS) is a hematopoietic stem cell disorder with an incompletely known pathogenesis. Long noncoding RNAs (lncRNAs) play multiple roles in hematopoiesis and represent a new class of biomarkers and therapeutic targets, but information on their roles in MDS is limited. Aims: here, we aimed to characterize lncRNAs deregulated in MDS that may function in disease pathogenesis. In particular, we focused on the identification of lncRNAs that could serve as novel potential biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Interestingly, NEAT1_2 expression tended to increase with advancing age (Figure S4). We therefore compared NEAT1 expression in CD34 + HSPCs from healthy people and patients with ASXL1-mutated myeloid neoplasms at ages 50-70 (Szikszai et al, 2020). Consistent with the mouse data, expression of NEAT1_2, but not total Neat1, was downregulated in human HSPCs with ASXL1 mutations (Figure 4D).…”
Section: Asxl1 Upregulates Neat1 Expression In the Nucleussupporting
confidence: 73%
“…Interestingly, NEAT1_2 expression tended to increase with advancing age (Figure S4). We therefore compared NEAT1 expression in CD34 + HSPCs from healthy people and patients with ASXL1-mutated myeloid neoplasms at ages 50-70 (Szikszai et al, 2020). Consistent with the mouse data, expression of NEAT1_2, but not total Neat1, was downregulated in human HSPCs with ASXL1 mutations (Figure 4D).…”
Section: Asxl1 Upregulates Neat1 Expression In the Nucleussupporting
confidence: 73%
“…Interestingly, Wang, S et al built a novel prognostic nomogram based on five lnc-RNAs in clear cell renal cell carcinoma, comprising AC026992.2, AC245041.2, LINC00524, LINC01956, and LINC02080 [ 46 ]. Previous work on lncRNA profiling also revealed that BOLA3-AS1 was associated with higher-risk myelodysplastic syndrome, which played an important role in the development of blood lineages such as platelets, erythrocytes, and myeloid cells [ 47 ]. However, the roles of AP003392.1 and AP001271.1 are yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) can play important roles in the development of multiple diseases (11,12). Moreover, lncRNAs participate in the prevention of AP.…”
Section: Introductionmentioning
confidence: 99%